Disability in adults with arthrogryposis is severe, partly invisible, and varies by genotype. (1st May 2018) - Dai, Shenhao; Dieterich, Klaus; Jaeger, Marie; Wuyam, Bernard; Jouk, Pierre-Simon; Pérennou, Dominic
Abstract : Objective: To understand the disability of adults with arthrogryposis multiplex congenita (AMC), a rare disease spectrum characterized by at least 2 joint contractures at birth in different body areas. Methods: This is a retrospective analysis of data for unselected persons with AMC referred to the French center for adults with AMC from 2010 to 2016. All underwent a pluriprofessional systematic and comprehensive investigation of deficits, activity limitation, and participation restriction according to the International Classification of Functioning, Disability and Health and genetic analysis when indicated. Participants were divided by amyoplasia and other AMC types. Results: Mean (SD) age of the 43 participants (27 female) was 33.2 (13.4) years; 28 had amyoplasia and 15 other types of AMC. Beyond joint stiffness, deformities, and muscle weakness, the well-known core symptoms that we quantified and for which first-line treatment involved technical aids, other less visible disorders that could contribute to severe participation restriction were particularly pain and psychological problems including anxiety, fatigue, difficulty in sexual life, altered self-esteem, and feelings of solitude. Severe respiratory disorders were infrequent and were linked to PIEZO2 mutations. Gait disorders were not due to respiratory impairment but to skeletal problems and were always associated with amyoplasia when severe. Functional independence was worse but respiratory and swallowing capacities were better with amyoplasia than other AMC types. Conclusion: This study describes disability patterns of a cohort of adults with AMC by genotype. The disability of adults with AMC is influenced by genotype, with important invisible disability.